Analisis atas pelaporan keuangan pada dinas pendidikan dan kebudayaan kabupaten Padang Pariaman - Amran, Elsa Fitri; Sari , Yesi Novita (Jurnal Indovisi, 2018)
The research was conducted at the Education and Culture Office of Padang Pariaman Regency which is a local government agency that carries out some of the Government's affairs in the field of education and culture. The purpose of this study is to determine the conformity of the Government's financial statements on the Education and Culture Office of Padang Pariaman Regency already with Government Regulation Law number 24 in 2005 on government accounting standards, analyzing financial statements using efficiency ratios, independence ratios, budget growth ratios, analyzing internal control systems in the process of preparing financial reports, analyzing the quality of human resources and educational background of civil states aparatus and employees as financial managers in the process of preparing reports finance in the Education and Culture Office of Padang Pariaman Regency. The method used in this study is by library study method and field research with related officials, after which the data has been collected is analyzed descriptively that comparing the actual situation with relevant theories, in order to obtain the results of research for the problems encountered related with the implementation of government financial reporting on Education and Culture Office of Padang Pariaman Regency. From the data analysis conducted, obtained the result that the government's financial report on the Education and Culture Office of Padang Pariaman Regency Already in accordance with Government Regulation number 24 in 2005; The efficiency ratio of the Education and Culture Office of Padang Pariaman Regency in 2016 is in efficient condition with the percentage ratio of 95.32%. The 2016 independence ratio is in the pattern of delegative relations. The 2016 budget growth ratio was positive growth with a 10% increase. Internal Control System has been done well with data integrity and documents or archives that have been stored well, the evaluation of the economy, efficiency, and effectiveness has been in accordance with the set targets. The quality of human resources at the Department of Education and Culture is good, civil states aparatus / Employees have skill and work experience long enough.